What Drives Utilization of Primary Care Facilities? Evidence from a National Facility Survey - Vu, Lan T.H.; Bales, Sarah; Bredenkamp, Caryn (Taylor and Francis, 2022)
This analysis aims to assess the association between commune health station (CHS) service availability/readiness and health service utilization. Data from the 2015 Vietnam District and Commune Health Facility Survey was used to build a series of multivariate negative binomial regressions to measure the association between domains of service availability/readiness and CHS's average number of visits per capita. Three domains of service availability/readiness are significantly associated with higher utilization rates: health infrastructure, basic equipment availability, and capacity to deliver services for non-communicable diseases. If all three modifiable CHS characteristics were to be improved from their current level, the predicted utilization rate of the CHS would be 3.3–3.7 times as high as current levels. Investments in improving facility infrastructure, making available essential equipment items, and enabling the CHS to provide hypertension and diabetes services would all likely increase health service utilization at CHS level.